Lytic and latent antigens of the human gammaherpesviruses Kaposi's sarcoma-associated herpesvirus and Epstein-Barr virus induce T-cell responses with similar functional properties and memory phenotypes - Bihl, Florian; Narayan, Murli; Chisholm, 3rd, John V; Henry, Leah M; Suscovich, Todd J; Brown, Elizabeth E; Welzel, Tania M; Kaufmann, Daniel E; Zaman, Tauheed M; Dollard, Sheila; Martin, Jeff N; Wang, Fred; et al. (Journal of virology, 2007)
The cellular immunity against Kaposi's sarcoma-associated herpesvirus (KSHV) is poorly characterized and has not been compared to T-cell responses against other human herpesviruses. Here, novel and dominant targets of KSHV-specific cellular immunity are identified and compared to T cells specific for lytic and latent antigens in a second human gammaherpesvirus, Epstein-Barr virus. The data identify a novel HLA-B57- and HLA-B58-restricted epitope in the Orf57 protein and show consistently close parallels in immune phenotypes and functional response patterns between cells targeting lytic or latent KSHV- and EBV-encoded antigens, suggesting common mechanisms in the induction of these responses.